1994
DOI: 10.1073/pnas.91.20.9436
|View full text |Cite
|
Sign up to set email alerts
|

Advanced glycation end products up-regulate gene expression found in diabetic glomerular disease.

Abstract: Several lines of evidence suggest that the excessive accumulation of extracellular matrix in the glomeruli of diabetic kidneys may be due to reactive intermediates forming between glucose and matrix proteins called advanced glycation end products (AGEs). Normal mice received AGEmodified mouse serum albumin i.p. for 4 weeks, and glomerular extracellular matrix, growth factor mRNA levels, and morphology were examined. We found that AGE induced an increase in glomerular extraceflular matrix al(IV) collagen, lamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
174
1
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 284 publications
(186 citation statements)
references
References 33 publications
9
174
1
2
Order By: Relevance
“…Plasma or serum levels of C-reactive protein (CRP) were measured by immunonephelometry (IMMAGE Nephelometer, Beckman Coulter). TNF␣ mRNA levels in mononuclear cells were measured by RT-PCR as described (31), and TNF␣ protein and VCAM-1 were measured by ELISA kits (BioSource International, Camarillo, CA and R & D Systems). sAGE levels were measured by CML-sensitive ELISA (4G9) (24,25).…”
Section: Methodsmentioning
confidence: 99%
“…Plasma or serum levels of C-reactive protein (CRP) were measured by immunonephelometry (IMMAGE Nephelometer, Beckman Coulter). TNF␣ mRNA levels in mononuclear cells were measured by RT-PCR as described (31), and TNF␣ protein and VCAM-1 were measured by ELISA kits (BioSource International, Camarillo, CA and R & D Systems). sAGE levels were measured by CML-sensitive ELISA (4G9) (24,25).…”
Section: Methodsmentioning
confidence: 99%
“…The mechanisms by which AGE binding to its receptor may lead to the pathological features of diabetic complications have begun to be explored. For instance, administration of AGE proteins to normal mice results in upregulation of the prosclerotic cytokine transforming growth factor (TGF)b in glomeruli, possibly mediating the increase in extracellular matrix gene expression and glomerular hypertrophy observed in this model [46]. In vitro studies by Doi et al [47] have suggested that platelet derived growth factor (PDGF) may also mediate the increase in extracellular matrix production by mesangial cells on exposure to AGE proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Neutralizing anti-TGF-b antibodies in vivo suppressed diabetes-related kidney growth [49]. In vivo studies have shown treatment with AGE-modified mouse serum albumin, generated in vitro, induced gene expression of type IV collagen and TGF-b1 in the glomeruli [15]. Intensive investigation into the pathogenesis of ECM accumulation in diabetes has consistently implicated the prosclerotic cytokine, TGF-b, as a key mediator [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Aminoguanidine (AG) [23], a hydrazine-like compound which blocks AGE formation by interacting with Amadori-derived products [24], has been shown to retard the development of diabetic microvascular and macrovascular complications in experimental animals [10,12,13,15,25,26]. In relation to diabetic nephropathy, AG attenuates the rise in albuminuria and prevents mesangial expansion in diabetic rats [27,28].…”
mentioning
confidence: 99%